A glucose-mediated antibiotic resistance metabolic flux from glycolysis, the pyruvate cycle, and glutamate metabolism to purine metabolism - Xiang, Jiao; Wang, Shi-wen; Tao, Yuan; Ye, Jing-zhou; Liang, Ying; Peng, Xuan-xian; Yang, Li-fen; Li, Hui (Frontiers in Microbiology, 2023)
Bacterial metabolic environment influences antibiotic killing efficacy. Thus, a full understanding for the metabolic resistance mechanisms is especially important to combat antibiotic-resistant bacteria. Here, isobaric tags for relative and absolute quantification-based proteomics approach was employed to compare proteomes between ceftazidime-resistant and -sensitive Edwarsiella tarda LTB4 (LTB4-RCAZ and LTB4-S, respectively). This analysis suggested the possibility that the ceftazidime resistance mediated by depressed glucose is implemented through an inefficient metabolic flux from glycolysis, the pyruvate cycle, glutamate metabolism to purine metabolism. The inefficient flux was demonstrated by the reduced expression of genes and the decreased activity of enzymes in the four metabolic pathways. However, supplement upstream glucose and downstream guanosine separately restored ceftazidime killing, which not only supports the conclusion that the inefficient metabolic flux is responsible for the resistance, but also provides an effective approach to reverse the resistance. In addition, the present study showed that ceftazidime is bound to pts promoter in E. tarda. Our study highlights the way in fully understanding metabolic resistance mechanisms and establishing metabolites-based metabolic reprogramming to combat antibiotic resistance.